Perilaku Pemilihan Makanan Jajanan Siswa SDIT Al Firdaus Purwodadi Berdasarkan Pengetahuan dan Sikap tentang Makanan Jajanan - Mahardika, Alviannisa Rizqi; Mutalazimah, Mutalazimah (Poltekkes Kemenkes Yogyakarta, 2024)
Background: School-age children have a habit of consuming snacks. Snack foods that do not meet health and nutritional requirements will reduce the health status of children. Objective: To analyze the relationship between knowledge and attitude with snacks and food-choice behavior at the Sekolah Dasar Islam Terpadu (SDIT) or Islamic Elementary School Al Firdaus Purwodadi. Methods: This cross-sectional observational study used a sample of 103 from a population of 335 students in grades III, IV, V, and VI SDIT Al Firdaus Purwodadi, which were taken by proportional stratified random sampling. Knowledge, attitude, and behavior data were taken using a questionnaire that met the validity and reliability tests. Data analysis used the Pearson product-moment correlation test. Results: The results showed that children's knowledge about the choice of snack foods in the less category by 33%. The attitude of children about snack choices who are less is 1.9% and the behavior of children in choosing food in the less category is 18.4%. There is a relationship between knowledge and attitudes in the behavior of choosing snacks (p=0.001) respectively. Conclusion: There is a relationship between knowledge, attitudes, and behavior about snacks among students at SDIT Al Firdaus Purwodadi.